KETERTARIKAN PENGGUNA MEDIA SOSIAL TERHADAP KONTEN VISUAL DI INSTAGRAM @himakom.uki - Litha, Trianna Sampe; Kreshan, Altisya (Kinesik, 2024)
The diversity of visual content on Instagram social media triggers users to repeatedly view and access uploads on the target social media. This is in the form of interest which causes a response that is processed first through a stimulus. In this case, it is in the form of visual content on social media Instagram @himakom.uki. This research uses a qualitative descriptive method with data collection techniques using interviews from informants determined based on purposive sampling techniques. This research aims to find out and analyze user’s interest in visual content on Instagram. By using analytical techniques, namely data reduction, data presentation and drawing conclusions, research results show that varied visual content tends to attract the attention of Instagram users to continuously search for information. This is in line with Stimulus, Organism and Response (SOR). Where the stimulus is in the form of a message, the organism is in the form of an Instagram user and the response is in the form of behavior to continuously view visual content uploaded on social media.